Effect of short- and medium-chain fatty acid mixture on polyhydroxyalkanoate production by Pseudomonas strains grown under different culture conditions - Szacherska, Karolina; Moraczewski, Krzysztof; Czaplicki, Sylwester; Oleskowicz-Popiel, Piotr; Mozejko-Ciesielska, Justyna (Frontiers in Bioengineering and Biotechnology, 2022)
Short- and medium-chain fatty acids (SMCFAs) derived from the acidogenic anaerobic mixed culture fermentation of acid whey obtained from a crude cheese production line and their synthetic mixture that simulates a real SMCFA-rich stream were evaluated for polyhydroxyalkanoate (PHA) production. Three individual Pseudomonas sp. strains showed different capabilities of growing and producing PHAs in the presence of a synthetic mixture of SMCFAs. Pseudomonas sp. GL06 exhibited the highest SMCFA tolerance and produced PHAs with the highest productivity (2.7 mg/L h). Based on these observations, this strain was selected for further investigations on PHA production in a fed-batch bioreactor with a SMCFA-rich stream extracted from the effluent. The results showed that PHA productivity reached up to 4.5 mg/L h at 24 h of fermentation together with the ammonium exhaustion in the growth medium. Moreover, the PHA monomeric composition varied with the bacterial strain and the type of the growth medium used. Furthermore, a differential scanning calorimetric and thermogravimetric analysis showed that a short- and medium-chain-length PHA copolymer made of 3-hydroxybutyric, -hexanoic, -octanoic, -decanoic, and -dodecanoic has promising properties. The ability of Pseudomonas sp. to produce tailored PHA copolymers together with the range of possible applications opens new perspectives in the development of PHA bioproduction as a part of an integrated valorization process of SMCFAs derived from waste streams.